Presentations of International Summer School on WEFE Nexus in Central Asia - International Center for Agricultural Research in the Dry Areas; International Water Management Institute; Bioversity International (2023)
The present report includes all the training materials from the International Summer School on WEFE Nexus in Central Asia in Tashkent